PURIFICATION AND BIOLOGICAL ACTIVITIES OF COMBINATION OF HEMI-SYNTHESIZED THIOSEMICARBAZONES OF MITRACARPUS SCABER ZUCC - Bouraima, BAMBOLA; Alban, HOUNGBEME Gouton; Louis, FAGBOHOUN; Sèdami, MEDEGAN; Fernand, GBAGUIDI Ahokanou (Universal Journal of Pharmaceutical Research, 2020)
Objective: The harvested Mitracarpus Scaber plants are identified in the national herbarium and registered under the number AA. 6252/HLB. During this work, three crude extracts are prepared from three organic solvents, namely dichloromethane; ethanol and hydroethanol in 50/50 v/v proportion. Methods: The respective alkaloid extracts obtained from the corresponding crude extracts served as substrates for the hemi synthesis of thiosemicarbazone totals from thiosemicarbazides. The three hemi-synthesis products obtained were tested on eight (08) strains of germs, namely E. coli ATCC 25922, S. aureus ATCC 25923, E. faecalis ATCC 22921, P. aeruginosa ATCC 27853, C. albicans ATCC 10231, S. typhi, K. pneumoniae and Dermatophilus 146. Results: The ethanolic extract of thiosemicarbazones exhibited the best bioactive activity and was found to be the most selective. By a series of bioguided chromatographies: TLC thin layer chromatography; CPA atmospheric pressure chromatography and medium pressure liquid chromatography. MPLC (medium pressure liquid chromatography), separation on dextran gel: Sephadex® LH20). The use of available spectral data, cross-checked with that of the literature, made it possible to identify and purify three (03) molecules of thiosemicarbazones, making it possible to study the biological activity of their combination. Conclusion: On the basis of results, this work has made it possible to confirm the concept which affirms that medicinal plants are libraries of several thousand molecules. Peer Review History: Received 11 October 2019; Revised 7 November; Accepted 29 December; Available online 15 January 2020 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Prof. Dr. Ali Gamal Ahmed Al-kaf , Sana’a university, Yemen, alialkaf21@gmail.com Prof. Dr. Amani S. Awaad , Prince Sattam Bin Abdulaziz University, Al-Kharj. KSA., amaniawaad@hotmail.com